PENINGKATAN PENGETAHUAN KELUARGA TERHADAP PERAWATAN PASIEN DI RUMAH DALAM MENCEGAH KOMPLIKASI PADA PASIEN STROKE DENGAN IMPLEMENTASI TELENURSING - Mira Asmirajanti; Azizah, Anik Hanifatul; Mustikawati, Intan Silviana; Romadhoni, Asisyafitri; Bahraini, Dwi; Pratama, Ariq; Syahputra, Agung Dwi (Universitas Mataram, 2024)
Stroke, one of the leading causes of neurological disability, has a significant impact on the patient's ability to perform daily activities. This community service aims to increase the knowledge of stroke patients' families about home care to prevent complications with the implementation of telenursing. This activity was held on February 6, 2024, in Desa Semanan, Jakarta Barat, involving 25 patients and their families, as well as Posbindu cadres. The activity began with coordination with partners to take care of permits and site reviews. Education was provided through presentations, demonstrations, and video tutorials on the care of stroke patients at home, followed by assistance through telenursing using WhatsApp groups. The evaluation was carried out with pre-test and post-test to measure the understanding of the patient's family. The results showed a significant increase in family knowledge by 44%. In conclusion, this education is effective in increasing family knowledge to improve the care of stroke patients at home, which is important in preventing complications and improving the quality of life of patients.